Delineation of Slavery in Selected Literature of Nepal - K. C., Durga Lal (Haimaprabha, 2023)
Slavery stands as the cultural practice, norms and values where one class entice, persuade and force another class to assist, work and Labor for the benefits of the former. It was a common practice in the world when people were not aware about their rights. Empowerment of people resulted the end of slavery in most of the countries. Slavery was eradicated from Nepal in 1981 B. S. by Rana Prime minister Chandra Shumsher Rana. It was just a legal declaration but it was a great challenge to end it practically. There were different types of slavery in the society. Kamaiya, Kamalari, Haruwa, Charuwa and Haliya traditions were prevalent in different parts of Nepal. This article explores the illustration of slavery in some selected literature of Nepal. This study analyses about how slavery is presented in the literature.